How Children’s Mentalistic Theory Widens their Conception of Pictorial Possibilities - Gilli, Gabriella M.; Ruggi, Simona; Gatti, Monica; Freeman, Norman H. (Frontiers in Psychology, 2016)
An interpretative theory of mind enables young children to grasp that people fulfil varying intentions when making pictures. It is not known when children widen their conception of artists’ intentions beyond that of picture-production, to include artists’ intention to show their pictures to others. We report studies centring on aspects of picture-exhibition, involving normal public display as well as the contrary intentions of hiding an original picture and of deceitfully displaying a forgery. Children aged between five and ten years viewed a brief video of an artist deliberately hiding her picture but her intention was thwarted when her picture was discovered and displayed. The first interview revealed that by eight years of age children were almost unanimous that a picture-producer without an intention to show her work to others cannot be considered to be an artist. Subsequent interviews revealed that the concept of exhibition widened to take others’ minds into account viewers’ critical judgements, and effects of forgeries on viewers’ minds. An increasingly mentalistic approach enables children to understand diverse possibilities in the art domain. The present technique of interpolating probes of typical possibilities between atypical intentions generated evidence that in middle childhood the foundations are laid for a conception of communication between artists’ minds and viewers’ minds via pictorial display.